Risking safety and rights: online sex work, crimes and 'blended safety repertoires'. (14th October 2018) - Campbell, Rosie; Sanders, Teela; Scoular, Jane; Pitcher, Jane; Cunningham, Stewart
Abstract: It has been well established that those working in the sex industry are at various risks of violence and crime depending on where they sell sex and the environments in which they work. What sociological research has failed to address is how crime and safety have been affected by the dynamic changing nature of sex work given the dominance of the internet and digital technologies, including the development of new markets such as webcamming. This paper reports the most comprehensive findings on the internet‐based sex market in the UK demonstrating types of crimes experienced by internet‐based sex workers and the strategies of risk management that sex workers adopt, building on our article in the British Journal of Sociology in 2007. We present the concept of 'blended safety repertoires' to explain how sex workers, particularly independent escorts, are using a range of traditional techniques alongside digitally enabled strategies to keep themselves safe. We contribute a deeper understanding of why sex workers who work indoors rarely report crimes to the police, reflecting the dilemmas experienced. Our findings highlight how legal and policy changes which seek to ban online adult services advertising and sex work related content within online spaces would have direct impact on the safety strategies online sex workers employ and would further undermine their safety. These findings occur in a context where aspects of sex work are quasi‐criminalized through the brothel keeping legislation. We conclude that the legal and policy failure to recognize sex work as a form of employment, contributes to the stigmatization of sex work and prevents individuals working together. Current UK policy disallows a framework for employment laws and health and safety standards to regulate sex work, leaving sex workers in the shadow economy, their safety at risk in a quasi‐legal system. In light of the strong evidence that the internet makes sex work safer, we argue that decriminalisation as a rights based model of regulation is most appropriate.